Capacity building of the Australian Aboriginal and Torres Strait Islander health researcher workforce: a narrative review - Shaun C. Ewen; Tess Ryan; Chris Platania-Phung (BMC, 2019)
Abstract Background This paper provides a narrative review that scopes and integrates the literature on the development and strengthening of the Australian Aboriginal and Torres Strait Islander health researcher workforce. The health researcher workforce is a critical, and oft overlooked, element in the health workforce, where the focus is usually on the clinical occupations and capabilities. Support and development of the Australian Aboriginal and Torres Strait Islander health researcher workforce is necessary to realise more effective health policies, a more robust wider health workforce, and evidence-led clinical care. This holds true internationally. It is critical to identify what approaches have resulted in increased numbers of Aboriginal and Torres Strait Islander people in health research, stronger local community partnerships with universities and industry, and research excellence and have contributed to evidence-led health workforce development strategies. Methods The search was for peer-reviewed journal articles between 2000 and early 2018 on capacity building of the Aboriginal and Torres Strait Islander health researcher workforce. Databases searched were CINAHL (EBSCO), PubMed, PsychINFO, LIt.search, and Google Scholar, combined with manual searches of select journals and citations in the grey literature. A coding scheme was developed to scan research coverage of various dimensions of health research capacity building. Results Twenty-four articles were identified. Eight focused on strengthening research capabilities of community members. A recurrent finding was the high research productivity of Aboriginal and Torres Strait Islander health researchers and strong interest in furthering research that makes a substantive contribution to community well-being. Action-based principles were derived from synthesis of the findings. Generally, research capacity building led to numerous gains in workforce development and improving health systems. Conclusions There is a shortage of literature on health researcher workforce capacity building. National-level research on capacity building strategies is needed to support the continued success and sustainability of the Australian Aboriginal and Torres Strait Islander health researcher workforce. This research needs to build on the strengths of Aboriginal and Torres Strait Islander researchers. It also needs to identify clear and robust pathways to careers and stable employment in the health workforce, and health researcher workforce more specifically. This need is evident in all settler colonial nations (e.g. Canada, United States of America, New Zealand), and principles can be applied more broadly to other minoritised populations.